The Effect Of Corporate Social Responsibility On Profitability With Leverage As Moderating Variable - Titi Dewi Warninda; Sakinah Faujiyah (Universitas Ahmad Dahlan, 2023)
Purpose- This study aims to analyze the effect of corporate social responsibility on the profitability of listed banks in Indonesia and analyze leverage as the moderating variable. Design/Methodology/Approach- This research uses data from 14 listed banks in the Indonesia Stock Exchange from 2017-2021. The equations to analyze the influence of corporate social responsibility and some control variables (firm size, capital adequacy ratio, leverage, and inflation) on profitability and the influence of leverage as a moderating variable are estimated using Fixed-Effect panel data regression. Findings- The results of this research show that firm size, capital adequacy ratio, leverage, and rate of inflation variables have a positive influence on profitability. Meanwhile, corporate social responsibility and the moderating effect of leverage do not significantly influence profitability. Research limitations/implications- The research findings are expected to become a reference for the investor and the bank management on the influence of corporate social responsibility on a listed bank's profitability and the effect of leverage as a moderating variable. Originality/value- As an intermediary, banks have different types of leverage than non-bank companies. This study analyzes the impact of corporate social responsibility with leverage as a moderating variable on the profitability of listed banks in the Indonesian Stock Exchange.